Pengaruh Tekanan, Kesempatan, Rasionalisasi dan Kemampuan terhadap Academic Fraud pada Mahasiswa (Studi Kasus Mahasiswa Universitas Trilogi) - Adinda Resty Reshita; Efendri Efendri (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to analyze respondents' perceptions about the influence of pressure, opportunity, rationalization and ability on academic fraud on Trilogy university students. The population is determined based on certain criteria totaling 1,205 people (respondents). From this population, the sample was calculated using the Slovin formula which resulted in a sample of 303 people who were randomly selected. Data processing uses Partial Least Square (PLS) with the WarpPls application. The results of the study concluded that pressure (P-Value 0.461) and opportunity (P-Value 0.076) had no partial effect on academic cheating, while rationalization (P-Value <0.001) and ability (P-Value <0.001) had a partially significant effect against academic cheating.